2021
DOI: 10.1007/s10339-021-01029-2
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making, cognitive functions, impulsivity, and media multitasking expectancies in high versus low media multitaskers

Abstract: In several studies, individuals who reported to frequently multitask with different media displayed reduced cognitive performance, for example in fluid intelligence and executive functioning. These cognitive functions are relevant for making advantageous decisions under both objective risk (requiring reflection and strategical planning) and ambiguous risk (requiring learning from feedback). Thus, compared to low media multitaskers (LMMs), high media multitaskers (HMMs) may perform worse in both types of decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…Media multitasking has undoubtedly become a daily habit nowadays. A number of studies have explored the relationship between media multitasking and cognitive abilities (Müller et al 2021;Ophir et al 2009;Van der Schuur et al 2015), but existing results are…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Media multitasking has undoubtedly become a daily habit nowadays. A number of studies have explored the relationship between media multitasking and cognitive abilities (Müller et al 2021;Ophir et al 2009;Van der Schuur et al 2015), but existing results are…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing number of studies exploring the relationship between media multitasking and cognitive abilities (e.g., Müller et al 2021 ; Ophir et al 2009 ; Uncapher and Wagner 2018 ; Van der Schuur et al 2015 ). However, it remains ambiguous how media multitasking relates to cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past two decades, studies of real-world multitasking have largely focused on measuring multitasking in the digital realm (e.g., concurrent use of multiple digital devices or platforms simultaneously), using self-report questionnaires such as the Media Multitasking Index (Ophir et al, 2009) and produced mixed results. On the one hand, those with higher levels of media multitasking have displayed poorer cognitive performance such as in attentional control and working memory, but also more mind wandering (e.g., Baumgartner et al, 2017;Müller et al, 2021, Ophir et al, 2009Ralph et al, 2014). On the other hand, studies have found that better media multitasking was related to better multisensory integration, the ability to integrate information from different modalities (e.g., sight and sound; Lui & Wong, 2012).…”
Section: Introductionmentioning
confidence: 99%